Recent Progress in the Understanding and Engineering of Coenzyme B12-Dependent Glycerol Dehydratase - Nasir, Abdul; Ashok, Somasundar; Shim, Jeung Yeop; Park, Sunghoon; Yoo, Tae Hyeon (Frontiers in Bioengineering and Biotechnology, 2020)
Coenzyme B12-dependent glycerol dehydratase (GDHt) catalyzes the dehydration reaction of glycerol in the presence of adenosylcobalamin to yield 3-hydroxypropanal (3-HPA), which can be converted biologically to versatile platform chemicals such as 1,3-propanediol and 3-hydroxypropionic acid. Owing to the increased demand for biofuels, developing biological processes based on glycerol, which is a byproduct of biodiesel production, has attracted considerable attention recently. In this review, we will provide updates on the current understanding of the catalytic mechanism and structure of coenzyme B12-dependent GDHt, and then summarize the results of engineering attempts, with perspectives on future directions in its engineering.